2021
DOI: 10.1177/2051570720984158
|View full text |Cite
|
Sign up to set email alerts
|

Green consumption in Vietnam: Effects of eco-certification, brand, and moderate incongruity of their origins on purchase intent

Abstract: In the mainstream of green consumption literature, it is asserted that information on eco-certification, brand, and country-of-origin has certain effects on consumer behavior. This study explores how eco-certification origin and brand origin would interact and influence the consumers’ purchase intent for green products. To achieve this objective, the authors conducted a 2 (eco-certification: domestic vs foreign) × 2 (brand: domestic vs foreign) between-subject experiment with 640 Vietnamese respondents. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Secondly, a favourable CEI could help to differentiate eco-products and increase the demand for them in the globalised market (Dekhili and Nguyen, 2021). Therefore, knowledge of country ecological dimensions provides avenues for communication on the favourability of the CEI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, a favourable CEI could help to differentiate eco-products and increase the demand for them in the globalised market (Dekhili and Nguyen, 2021). Therefore, knowledge of country ecological dimensions provides avenues for communication on the favourability of the CEI.…”
Section: Discussionmentioning
confidence: 99%
“…According to Götze and Brunner (2019), individuals are uncertain about the production practices used in the creation of products and in environmental conditions generally. Hence, consumers are seeking further information about the COO of eco-products they purchase (Dekhili and Nguyen, 2021). Consequently, products that incorporate sustainability attributes are increasingly attractive to them (Kletzan et al , 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Eco labels and certifications are also catching attention of researchers in there and there is consensus among them regarding eco labels (Dekhili & Achabou, 2014;Dropulić & Krupka, 2020;de Medeiros & Ribeiro, 2017;Dekhili & Nguyen, 2021;Nekmahmud & Fekete-Farkas, 2020). Contrary to popular belief, an empirical study by Dekhili (2014) on French consumers found that consumers trusted self-declared eco labels more than third party certifications There is scant literature in India on eco labels and certifications affecting consumer purchase behaviour for green products.…”
Section: Quality and Pricementioning
confidence: 99%